The Mediating Effect of Organizational Citizenship Behaviour on Relationship Between Self Efficacy and Employee Performance - Sakti, Ramalio Fahridho; Rini, Hesty Prima (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examined the impact of self-efficacy on employee performance, specifically through organizational citizenship behavior. The goal was to understand how these factors influenced employee performance, considering that work often went beyond job descriptions. The study used a quantitative approach, with the population drawn from the employees of PT SIER, and purposive sampling was employed to select participants from the Development and PIER Area divisions. Data were collected through a questionnaire based on indicators of each research variable and analyzed using SmartPLS software. The findings revealed that self-efficacy directly affected employee performance, while self efficacy has indirect influence on employee performance when through organizational citizenship behavior. Overall, this research highlighted the significance of enhancing employee self-efficacy to improve performance in the modern workplace.